Stories of change in nutrition: Lessons from a new generation of studies from Africa, Asia and Europe - Headey, Derek D.; Gillespie, Stuart; Avula, Rasmi; Becquey, Elodie; Nisbett, Nicholas; Harris, Jody (Springer, 2023)
How does nutrition improve? We need to understand better what drives both positive and negative change in different contexts, and what more can be done to reduce malnutrition. Since 2015, the Stories of Change in Nutrition studies have analysed and documented experiences in many different African and Asian countries, to foster empirically-grounded experiential learning across contexts. This article provides an overview of findings from 14 studies undertaken in nine countries in South Asia, sub-Saharan Africa, and Europe between 2017 and 2021. The studies used a combination of methods, including regression-decomposition analyses of national datasets to assess determinants of nutritional change; policy process and food environment analyses; and community-level research assessing attitudes to change. This article takes a narrative synthesis approach to identify key themes across the studies, paying particular attention to multisectoral determinants, changes in the food environment, the role of structural factors (including longstanding social inequities), and changes in political commitment, cross-sectoral coherence and capacity. Given the inherent multisectoral nature of nutrition, many countries are experimenting with different models of ensuring coherence across sectors that are captured in this body of work. The relative immaturity of the policy sector in dealing with issues such as obesity and overweight, and associated influences in the wider food environment, adds a further challenge. To address these interrelated issues, policy must simultaneously tackle nutrition’s upstream (social/economic/equity) and downstream (health and dietary) determinants. Studies synthesised here provide empirically-driven inspiration for action.